The Role of Government Public Relations in Stakeholder Collaboration for Sustainable Tourism (Study Case of Ciletuh-Palabuhanratu Geopark) - Siti Choerunnisa; Neneng Nurlaela Arief (Publikasi Indonesia, 2026)
Ciletuh-Palabuhanratu-Geopark (CPUGGP) is a prestigious site as a UNESCO Global Geopark that is challenged by governance practices to convert formal recognition into sustainable stakeholder management. This research seeks to uncover the policy reasons for participation stagnation and the distinctive essence of the governance model. Adopting a qualitative approach with a case study method, this study conducts in-depth interviews with the Pentahelix actors and processes the data through the fusion of the IAP2 Spectrum of Public Participation and the Four Models of Public Relations. The results display an obvious structural imbalance: The government is in the central